2012
DOI: 10.1097/tp.0b013e3182445e9d
|View full text |Cite
|
Sign up to set email alerts
|

Generic Immunosuppression in Solid Organ Transplantation

Abstract: The introduction of generic immunosuppressant medications may present an opportunity for cost savings in solid organ transplantation if equivalent clinical outcomes to the branded counterparts can be achieved. An interprofessional working group of the Canadian Society of Transplantation was established to develop recommendations on the use of generic immunosuppression in solid organ transplant recipients (SOTR) based on a review of the available data. Under current Health Canada licensing requirements, a demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 68 publications
3
49
0
1
Order By: Relevance
“…In particular, the generic product must show that the rate (i.e., maximum concentration, C max ) and extent (i.e., the area under the concentration-time curve [AUC]) to which the active ingredient becomes available at the site of drug action is comparable with the innovator drug under similar conditions. However, transplant societies have raised concerns regarding the validity of extrapolating data derived from healthy subjects to the target patient populations [8][9][10] . Indeed, although most of the generic CsA conversion trials in stable renal transplant recipients found the tested products to have similar pharmacokinetic profiles compared to Neoral [11][12][13][14] , few others have reported significant differences between generic and innovator products [15,16] .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the generic product must show that the rate (i.e., maximum concentration, C max ) and extent (i.e., the area under the concentration-time curve [AUC]) to which the active ingredient becomes available at the site of drug action is comparable with the innovator drug under similar conditions. However, transplant societies have raised concerns regarding the validity of extrapolating data derived from healthy subjects to the target patient populations [8][9][10] . Indeed, although most of the generic CsA conversion trials in stable renal transplant recipients found the tested products to have similar pharmacokinetic profiles compared to Neoral [11][12][13][14] , few others have reported significant differences between generic and innovator products [15,16] .…”
Section: Introductionmentioning
confidence: 99%
“…12 Comprehensive data on conversion from generic to brand tacrolimus are not readily available. [18][19][20][21][22] A recent tacrolimus conversion study did identify a significantly lower concentration to dose ratio. 18 This phenomenon was seen in nearly 40% of the kidney transplantation recipients receiving generic tacrolimus.…”
Section: Article In Pressmentioning
confidence: 95%
“…Unfortunately, this has not been the real life experience in a market with eight generic forms of tacrolimus. [17][18][19][20][21][22] Patients frequently present having been converted to generics without any notification or explanation by their local pharmacist. In our experience and that of other programs identified multiple long-term stable patients that have presented in acute rejection having been converted by their pharmacist without careful trough monitoring resulting in subtherapeutic trough levels.…”
Section: Article In Pressmentioning
confidence: 99%
“…Pharmacokinetic disparities were reported among several cyclosporine preparations in African Americans and in children [8] . The method of determining bioequivalence may not be adequate for immunosuppressive drugs, since it does not include actual transplant patients [10] .…”
Section: Discussionmentioning
confidence: 99%